1987
DOI: 10.1288/00005537-198708000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Use of human amniotic membrane in otolaryngologic practice

Abstract: Human amnion is a readily available allograft with low antigenicity, high antimicrobial potential, and the ability to foster cpithelialization. We have used human amniotic membrane in our department for replacing nasal mucosa in Rendu‐Osler‐Weber disease, as tympanic membrane grafts, and for covering head and neck sites after flap necrosis. Our experience shows moderate success for management of severe epistaxis and excellent results in covering surfaces after flap necrosis. Use of amnion in eardrum perforatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…It has been used to treat variable diseases such as non-healing skin ulcers, vaginal atresia, and severe ocular surface disease [9,35]. Moreover, it can serve as adjunctive tissue to reduce surgical adhesions in abdominal surgery and otolaryngologic surgery [25,29,36]. Furthermore, AM is an immuneprivileged tissue and rarely causes immunologic rejection [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to treat variable diseases such as non-healing skin ulcers, vaginal atresia, and severe ocular surface disease [9,35]. Moreover, it can serve as adjunctive tissue to reduce surgical adhesions in abdominal surgery and otolaryngologic surgery [25,29,36]. Furthermore, AM is an immuneprivileged tissue and rarely causes immunologic rejection [15].…”
Section: Introductionmentioning
confidence: 99%
“…Application of amniotic membrane has been carried out with satisfactory results on conjunctival defects reconstruction, ear reconstruction surgery, and vaginal epithelization. [17][18][19] Amniotic membrane has also been used to prevent adhesion in abdominal or pelvic surgery. 20,21 Another study showed that amniotic membrane induces down-regulation of transforming growth factor-beta (TGF-β), which has a role in the process of wound healing by triggering fibroblasts and macrophages recruitment and stimulates collagen production.…”
Section: 10mentioning
confidence: 99%
“…15,16 Amniotic membrane also gave satisfactory result on conjunctival defect reconstruction, ear reconstruction, vaginal epithelialization, and abdominal surgery. [17][18][19][20][21] The use of amniotic membrane on tendon repair has been developed in recent years. Bennett, et al 22 reported that amniotic membrane may reduce adhesion by suppressing the number of fibroblasts and macrophages in wound healing process.…”
Section: -25mentioning
confidence: 99%
“…HAM has also been used to promote healing in corneal diseases such as chemical and thermal burns, neurotrophic ulcers, persistent epithelial defects, shield ulcers, microbial keratitis, band keratopathy and bullous keratopathy (Dua et al, 2004, Tosi et al, 2005a, Tosi et al, 2005b. Furthermore, the use of HAM as a biomaterial has not been confined to ophthalmologyit is also widely used in general surgery and wound treatment, e.g., for burned skin, bedsores, ulcers (Faulk et al, 1980), and in head and neck surgery (Zohar et al, 1987). More recently, HAM has been used as a culture substrate for ex vivo cultured LSC transplantation.…”
Section: Amniotic Membrane Transplantationmentioning
confidence: 99%